THE INFLUENCE OF WORK MOTIVATION AND DISCIPLINE ON EMPLOYEE PERFORMANCE AT THE HRGA DEPARTMENT OF PT. OTTO PHARMACEUTICAL INDUSTRY - Ilham Setiawan Ramdani; Kurhayadi Kurhayadi; Tuti Asmala (SEAN Institute, 2023)
This research is motivated by the non-optimal performance shown by the employees of the Pharmaceutical Company PT. OTTO Pharmaceutical Industries, HRGA Department. This study aims to examine the effect of work motivation and discipline on employee performance at the Pharmaceutical Company PT. OTTO Pharmaceutical Industries, HRGA Department. The independent variables consist of work motivation and discipline, while the dependent variable is employee performance. This type of research is included in quantitative research, while the research method used is descriptive and verification methods. The research population is all employees of the Pharmaceutical Company PT. OTTO Pharmaceutical Industries, HRGA Department. The sampling technique is non-probability sampling using saturated sampling, so that the number of samples is 38 people. The data analysis used is multiple linear regression analysis. The results showed that work motivation and discipline had a positive and significant effect on employee performance. The magnitude of the effect of work motivation and discipline on employee performance is 70.7%.